Pembiayaan Bermasalah Pada Bank Syariah: Strategi Penanganan Dan Penyelesaiannya - Ubaidillah Ubaidillah (Fakultas Ekonomi dan Bisnis Islam (FEBI), Universitas Islam Negeri Prof. K.H. Saifuddin Zuhri Purwokerto, 2018)
Islamic banks in Indonesia are currently experiencing significant development, but this must also be balanced with good banking regulations and management, including handling problematic financing. Problematic financing has an unfavorable impact on Islamic law, the danger of financing problems, namely the non-repayment of financing given in part or in whole. The greater the problematic financing faced by the bank, the lower the level of operational health of the bank, the decrease in the quality of financing and the soundness of the bank affecting financial liquidity and solvency, ultimately affecting the trust of depositors or even prospective customers. The greater the amount of financing problematic, the greater the amount of reserve funds that must be provided, and the greater the bank's responsibility for holding a reserve fund, because the losses borne by the bank will reduce bank capital. The purpose of this paper is intended to be information or even input to Islamic bank academics and practitioners on how to deal with or strategies and also to resolve problematic financing.